Extraction conditions of polyphenol oxidase from banana peel - Baghdad Science Journal (مجلة بغداد للعلوم)
Polyphenol oxidase (PPO) is an enzyme containing copper, presents in various fruits and vegetables. It is responsible for the browning reactions when the cells are damaged during handling. The best conditions for extraction of polyphenol oxidase from banana peel was by using an extraction buffer containing phosphate buffer (0.05 M, pH 7), 0.01 M ascorbic acid and 0.5% polyethylene glycol, with extraction ratio 1:4 (w:v) for one minute by using blender. The enzyme activity was measured spectrophotometrically at 425 nm. PPO was studied to prevent the browning of banana peel which results in the loss of their marketability. The aim of this study was to determine the optimum conditions for polyphenol oxidase extraction from banana peel.